Peace and the Rule of Law: A Brief Theoretical Overview - Avramović, Dragutin (NBP. Nauka, bezbednosti, policija, 2022)
Having in mind that peace is a basic, universal social and legal value and a substantial prerequisite for realising all other values, the author observes the complex relationship between peace and the rule of law. In that relationship of mutual dependence, one of the disputable matters could be the fact that the issue resembles a chicken-and-egg dilemma: which of the two values is the preceding factor, which is older, which should be considered the cause and which the consequence. Is peace a necessary environment for the rule of law establishing, or the rule of law is a necessary prerequisite for peace? The answer to this question depends primarily on how the rule of law is perceived.Following the prevalent view that the rule of law is a formal/material concept, which implies that it has both institutional and value aspects, the author takes a standpoint that the value-openness of the rule of law concept should be regarded as its advantage rather than a weakness. The author criticises the one-sided perception of the rule of law based exclusively on the ideology and values of liberalism, and the tendency among western countries to present that vision of the rule of law as the only one that can ensure peace. According to the position of liberal scholars, without ‘liberal peace’, war and disorder would govern. However, the reality proves that imposition and export of a liberal version of the rule of law and the tendency to establish universal ‘liberal peace’ could also feed wars and conflicts.Correlation between peace and the rule of law is required but is not necessary (if one perceives the rule of law in its ‘thinnest’ form – the existence of an order). However, without peace, it is impossible to establish any kind of value-based ‘thick’ rule of law. On the other hand, no one-sided value-burdened vision of the rule of law is a necessary prerequisite for the existence of peace and order. The author believes that if there is a wish to take a step in the direction of ‘perpetual peace’ in Kant’s sense, the necessary presumption is tolerance and open-mindedness toward different ideological (value) models of the rule of law.
Keywords: Social values; Peace; War; Rule of Law; Right of the Stronger.